Environmental Damage Risk Control: A Study of Hadith - Azmi, Ulil; Yarrahman, Fajri (Tasamuh: Jurnal Studi Islam, 2025)
Environmental damage is an urgent global problem, with impacts that threaten the sustainability of our planet. This research aims to explore the teachings in the hadith related to the control of environmental damage risks. By integrating these teachings into modern environmental policies and practices, this research aims to contribute to developing a more sustainable and ethical approach to environmental management. The results of the study show that the teachings of Hadith can be a strong foundation for increasing environmental awareness, encouraging environmentally friendly behavior, and strengthening community involvement in environmental conservation efforts. As such, this research provides theoretical insights and offers practical guidance for facing the environmental challenges we face today.